CLASSROOM SETTING FOR INCLUSIVE PRESCHOOL (Case Studies In Al Falah Kindergarten, Ciracas, East Jakarta) - Adiarti, Wulan (Indonesian Journal of Early Childhood Education Studies, 2012)
This study aim to determined Inclusive classroom environment setting in Al Falah Kindergarten, Ciracas, Jakarta Timur. The research was taken in Al Falah Kindergarten consisting of 36 children. The research model used was qualitative model, of case study type. Research  steps  taken  uses  Spratleys  phased  forward  flow,  having  the  following  twelve research phases: (1) social status determination , (2) participatory observation, (3) ethnography notations, (4) descriptive observation, (5) domain analysis,(7) taxonomy analysis, (8) selective observation, (9) component analysis, (10) theme analysis, (11) discuss behavioral culture, (12) write down the ethnography. Data were collected by observing, interviewing and document analysis.  The research result  shows inclusive  class  environmental setting  was  done  while keeping the ideal ratio, playzone sizing, children mobility space, playzone ruling, inter center boundary, children grouping, variations of activity area, toy and play tool classification.